Hubungan antara Loneliness dengan Online Friendship pada Remaja di Sumatera Barat - Illahi, Amanda Permata; Primanita, Rida Yanna (Lembaga Yasin AlSys, 2025)
Loneliness can affect the way adolescents build and maintain social relationships, including in online interactions. This study aims to explain the relationship between loneliness and online friendship among adolescents in West Sumatra. A quantitative correlational approach was used, with a sample of 385 adolescents aged 15–19 years residing in West Sumatra, selected through convenience sampling. Participant criteria included having at least one online friend with whom they actively communicate via social media or instant messaging. The research instruments comprised a loneliness scale adapted into Indonesian by Gultom et al. (2024) and an online friendship scale developed by Ratri and Helmi (2023). Correlation analysis yielded an r value of 0.240 with a significance of p = 0.000 (p < 0.05), indicating a significant relationship between loneliness and online friendship among adolescents in West Sumatra. These findings suggest that levels of loneliness are positively associated with adolescents’ involvement in forming online friendships and highlight the importance of considering digital-based social interventions for youth development.